The usage features of multifrequency space-time signals in super-fast scanning radar with active phased antenna array - Gorshkov, V. K.; Leonov, I. N.; Sedyshev, Y. N.; Shevchenko, A. F.; Tyutyunnik, V. A. (Видавництво Національного університету "Львівська політехніка", 2009)
The usage features of multifrequency (MF) space-time signals (STS) which are formed by transmitter active phased antenna array (APAA) radar with angular super fast scanning (STS) in with paper are examined. The STS structural, correlation features and its interrelation with parameters of MF modulation and APAA characteristics are determined. It is shown that the usage of complex partial signal in each radiation element in association with suitable partial waveform can realize a synthesis (reconstruction) of transmitter APAA directional characteristic in receiver by returned signals. Reliability of the results is confirmed by simulation modeling on different partial signals.
Keywords: antenna array; multifrequency space-time signals; super fast scanning radar